Advances in Implantable Optogenetic Technology for Cardiovascular Research and Medicine - Madrid, Micah K.; Brennan, Jaclyn A.; Yin, Rose T.; Knight, Helen S.; Efimov, Igor R. (Frontiers in Physiology, 2021)
Optogenetic technology provides researchers with spatiotemporally precise tools for stimulation, sensing, and analysis of signaling and function in cells, tissues, and organs. These tools can offer low-energy and localized approaches due to the use of transgenically expressed light-gated opsins such as the cation channel Channelrhodopsin-2 (ChR2). While the field began with many neurobiological accomplishments it has also evolved exceptionally well in animal cardiac research in vitro, and to some degree in vivo. Implantable optical devices are being extensively developed to study particular electrophysiological phenomena with the precise control that optogenetics provides. In this review, we highlight recent advances in novel implantable devices and their application in cardiac optogenetics research. Furthermore, we also emphasize the difficulties in translating this technology towards clinical applications and discuss potential solutions for successful clinical translation.